Efficacy of Preemptive Analgesia in Reducing Postoperative Pain Scores - Nimra Ishaq, Muhammad Zafar Iqbal, Varda Balouch, Gohar Latif, Muhammad Aslam, Muhammad Hadi Khan, (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Post-operative pain is one of the more frequent post-operative complaints following surgery and can further hinder recovery, make the patient feel uncomfortable and may lead to the need for further pain medications. The preemptive analgesic approach involves preemptively treating the pain pathway with analgesic drugs to prevent central sensitization. This approach could be helpful for postoperative pain management and reduce the need for rescue analgesics. Objective: To determine the efficacy of preemptive analgesia in reducing postoperative pain scores among patients undergoing elective surgical procedures. Methods: This comparative study was conducted at the Department of Surgery/ Anaesthesia Mirpur Divisional Headquarters Teaching Hospital Mirpur AJK from July 2022 to July 2023. All 92 were patients who were undergoing elective surgery and were split evenly into two groups. Forty-six patients were put into Group A and 46 patients into Group B, each group having patients who were given preemptive analgesia prior to surgical incision and conventional postoperative analgesia respectively. Visual Analogue Scale (VAS) was used for the assessment of postoperative pain at 1, 2, 4, 6, 12 and 24 hours after surgery. Analgesic requirement for rescue, time to first rescue analgesic, total analgesia consumption, patient satisfaction and adverse effects were also documented. The data were analyzed using SPSS version 25, with a p value < 0.05 was regarded as statistically significant. Results: Patients in the preemptive analgesia group had significantly lower mean postoperative pain scores at all observed time intervals compared with the control group. At 1 hour, the mean pain score was 3.1 ± 1.0 in Group A and 5.2 ± 1.3 in Group B. At 24 hours, the mean pain score was 2.1 ± 0.8 in Group A and 3.0 ± 1.0 in Group B. Rescue analgesia was required in 16 (34.8%) patients in Group A compared with 31 (67.4%) patients in Group B. The time to first rescue analgesia was also longer in the preemptive analgesia group. Patient satisfaction was higher in Group A, while adverse effects were comparable between both groups. Conclusion: Preemptive analgesia was effective in reducing postoperative pain scores and rescue analgesic requirement during the first 24 hours after surgery. It also improved patient satisfaction without increasing major adverse effects. Preemptive analgesia should be considered as part of a planned multimodal strategy for postoperative pain management. Keywords: Preemptive analgesia, postoperative pain, Visual Analogue Scale, rescue analgesia, pain management, elective surgery.